a4b1 integrin associates with VEGFR2 in CLL cells and contributes to VEGF binding and intracellular signaling - Gutiérrez González, Alejandra; Aguilera Montilla, Noemí; Ugarte Berzal, Estefanía; Bailón, Elvira; Cerro Pardo, Isabel; Sánchez Maroto, Clara; García Campillo, Lara; García Marco, José A.; García Pardo, Ángeles (My University, 2024)
In chronic lymphocytic leukemia (CLL), a4b1 integrin (the main a4 heterodimer in CLL) and vascular endothelial growth factor (VEGF) share several pathological properties, including involvement in cell migration and survival.1-8 Accordingly, elevated expression of a4 integrin ($30% cells) constitutes an adverse prognostic marker9 and VEGF serum levels increase with CLL progression and could also have prognostic value.5,7 CLL cells express VEGF receptor 1 (VEGFR1), VEGFR2, and VEGFR3 receptors.5 VEGFR2 is the main signaling receptor in response to VEGF165 and its elevated expression correlates with CLL aggressivenes.5,10 Previous studies in endothelial cells have demonstrated interactions and functional cross talk between integrins (avb3, a9b1, a3b1, a5b1) and the VEGF/VEGFR2 system, including integrin-mediated adhesion to VEGF and VEGF-induced integrin activation.11-13 Moreover, shedding of syndecan-1 in endothelial cells induced coupling of a4b1 integrin and VEGFR2, VEGFR2 activation, and angiogenesis.14 It is not known whether a4b1 interacts with VEGF/VEGFR2 or/and contributes to VEGF functions in CLL and we have addressed this in the present study